The Correlation Between Students’ Writing and Students’ Speaking Abilities of 9th Grades Students in Recount Text at SMP Muhammadiyah 2 Pekanbaru - Asyasa, Nur; Niah, Siti; Syahfutra, Wandi (UIR Press, 2024)
The correlation between the writing and speaking abilities of students at SMP Muhammadiyah 2 Pekanbaru in recount text was the primary focus of this research. The purpose of this study was to determine the significance of the relationship between students' writing and speaking abilities in English recount texts. This study used quantitative methods. The subjects in this study are the SMP Muhammadiyah 2 Pekanbaru class IX students for the academic year 2023. The whole class IX of SMP Muhammadiyah 2 Pekanbaru becomes the sample for this study, which adopts total sampling technique. used two tests: a speaking and writing test on recount text. The findings indicated that students' writing got low score of 50 and a high score of 95. In contrast, the maximum score for students' recount text speaking ability was 90, while the lowest score was 50. Moreover, correlation coefficient found that students' writing and students' speaking abilities in recount text have a positive correlation, and the correlation between those variables were high. The study recommended that students should do more practice in writing to make them more understandable and able to construct a good sentence. Besides that, the students should practice speaking every time to improve their speaking.